2016
DOI: 10.1002/2015jd024401
|View full text |Cite
|
Sign up to set email alerts
|

On the composite response of the MLT to major sudden stratospheric warming events with elevated stratopause

Abstract: Based on a climate-chemistry model (constrained by reanalyses below~50 km), the zonal-mean composite response of the mesosphere and lower thermosphere (MLT) to major sudden stratospheric warming events with elevated stratopauses demonstrates the role of planetary waves (PWs) in driving the mean circulation in the presence of gravity waves (GWs), helping the polar vortex recover and communicating the sudden stratospheric warming (SSW) impact across the equator. With the SSW onset, strong westward PW drag appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
201
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(239 citation statements)
references
References 67 publications
19
201
2
Order By: Relevance
“…Tomikawa et al () reported PW activity in the upper stratosphere at high latitudes following a SSW event. The numerical studies (Chandran et al, ; Limpasuvan et al, ) showed PW activities in the MLT after the onset of major SSW events, which was distinct from PWs in the stratosphere, and the presence of the PWs was confirmed based on observations from sounding of the atmosphere using the broadband emission radiometry (SABER) instrument on board Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics (TIMED) satellite (Chandran et al, ). Hence, they suggested that the PWs may originate from jet instability in the winter polar region.…”
Section: Introductionmentioning
confidence: 98%
“…Tomikawa et al () reported PW activity in the upper stratosphere at high latitudes following a SSW event. The numerical studies (Chandran et al, ; Limpasuvan et al, ) showed PW activities in the MLT after the onset of major SSW events, which was distinct from PWs in the stratosphere, and the presence of the PWs was confirmed based on observations from sounding of the atmosphere using the broadband emission radiometry (SABER) instrument on board Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics (TIMED) satellite (Chandran et al, ). Hence, they suggested that the PWs may originate from jet instability in the winter polar region.…”
Section: Introductionmentioning
confidence: 98%
“…The strength of the Arctic vortex in the mesosphere is correlated with the amount of EPP‐NO x that descends into the polar winter stratosphere (Randall et al, ). The Arctic Januaries of 2004, 2006, 2009, 2010, 2012, and 2013 had prolonged SSW events (Kishore et al, ; Limpasuvan et al, ) whereby unusual planetary wave (PW) and GW filtering persisted to create a meteorological regime in the MLT that was undocumented prior to 2004. It is now understood that prolonged stratospheric easterlies allow GWs with westerly phase speeds to propagate up to the mesosphere and break, where they lead to a strengthening of the westerly winds associated with the vortex in the upper mesosphere (Hauchecorne et al, ; Manney et al, , ; Siskind et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Sudden stratospheric warmings lasting for more than 10 days occurred in January 2004, January 2006, and January 2009. These warmings were followed by an elevated stratopause and strong and long-lasting mesospheric and upper stratospheric descent (Randall et al, 2006Orsolini et al, 2010;Limpasuvan et al, 2016). They will be called strong sudden stratospheric warmings in the following.…”
Section: -2010mentioning
confidence: 99%
“…These warmings were followed by long-lasting downwelling in the mesosphere and upper stratosphere enabled by a strong polar vortex re-forming after the event. It was shown from both observations (Siskind et al, 2007;Orsolini et al, 2010) and model results (Limpasuvan et al, 2016) that this period of enhanced downwelling was characterized by the formation of an elevated stratopause in the upper mesosphere.…”
mentioning
confidence: 99%